Farmers’ Access to Farm Programs of Bangladesh Betar: An Evaluation of Effectiveness - Mahedi Hasan , Nazrul Islam Mondal , Nurul Islam; Aminul Hoque (Indian Journal of Extension Education, 2017)
Different forms of farm programs (FP) have been being developed and aired by Bangladesh Betar (BB) for decades to hasten the development of agriculture and the farming communities of Bangladesh. These programs are in dire need of academic study for in-depth evaluation to discern their effectiveness. This study was supposed to reveal the effectiveness of the FP of BB in respect of the extent to which it reaches the farmers of Bangladesh. Data and necessary information were collected by means of document analysis and survey methods. A sample of 465 respondents was selected for questionnaire survey. Frequency distribution and z-test for significance test of proportions were done for data analysis. It was divulged that the FPs of BB were ineffectual because they failed to reach 93.33 per cent of the farmers. Radio set, a culturally unfit device was possessed by only 4.30 per cent of the farmers. Most of the farmers were accustomed to unauthorized sources (salesman and fellow farmers) of farm information. Avast majority of the respondents were insolent towards the authorized extension agents and departments. The unconsciousness regarding the importance of farm knowledge and their mindset were the most influencing factors for listening to the FPs. Initiatives were must to change the long cherished mindset of the farmers and culturally fit devices were to be patronized in receiving the radio FPs.